Oscillation in neutral equations with an ?integrally small? coefficient - J. S. Yu; Ming-Po Chen (International Journal of Mathematics and Mathematical Sciences)
Consider the neutral delay differential equationddt[x(t)-P(t)x(t-t)]+Q(t)x(t-d)=0,???t=t0(*)Where P, Q?C([t0,8],R+), t?(0,8) and d?R+. We obtain several sufficient conditions for the oscillation of all solutions of Eq. (*) without the restriction ?t08Q(s)ds=8.